Thiourea-Ammonium Chloride Mediated Knoevenagel Condensation as an Intermediate in the Synthesis of Pyrimidine Scaffolds under Solvent-free Condition - Rayate, Ankita M.; Gaware, Manoj R. (Letters in Organic Chemistry, 2024)
In this paper, we have reported solvent solvent-free method for Knoevenagel condensation reaction of various aldehydes with active methylene compounds using thiourea and ammonium chloride. The developed method demonstrated high efficiency in the formation of C-C bond. The reaction proceeds smoothly under mild and solvent-free conditions and the products obtained are in excellent yield in very short duration. This method is applicable to a wide range of aldehydes with active methylene compounds.
Keywords: Ethyl cyanoacetate